2015
DOI: 10.1016/j.scitotenv.2015.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of antimony, arsenic and lead at a former antimony mine, Glendinning, Scotland

Abstract: HIGHLIGHTS• Solid phase speciation of antimony, arsenic, lead and iron differed between sites.• Elevated soil porewater antimony concentrations were linked to DOM and spoil leaching.• Leaching from spoil resulted in elevated antimony concentrations in stream water. AbstractElevated concentrations of antimony (Sb), arsenic (As) and lead (Pb) in upland organic-rich soils have resulted from past Sb mining activities at Glendinning, southern Scotland. Transfer of these elements into soil porewaters was linked to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 48 publications
4
27
0
Order By: Relevance
“…Very high concentrations of Sb in soils, over 9000 mg kg −1 , were also reported from mine sites in Dúbrava, Slovakia (Hiller et al 2012 ), and the data up to 4400 mg kg −1 Sb were recorded from Su Suergiu in Sardinia, Italy (Cidu et al 2014 ). Macgregor et al ( 2015 ) identified the sites with soil Sb concentrations up to 222 mg kg −1 in the surroundings of Glendinning mine (Scotland). Smelting activity can also cause soil contamination with Sb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very high concentrations of Sb in soils, over 9000 mg kg −1 , were also reported from mine sites in Dúbrava, Slovakia (Hiller et al 2012 ), and the data up to 4400 mg kg −1 Sb were recorded from Su Suergiu in Sardinia, Italy (Cidu et al 2014 ). Macgregor et al ( 2015 ) identified the sites with soil Sb concentrations up to 222 mg kg −1 in the surroundings of Glendinning mine (Scotland). Smelting activity can also cause soil contamination with Sb.…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary study (Lewińska et al 2017 ), carried out in the surroundings of the only historical stibnite (antimonite) mine in the Polish part of the Sudetes (Mączka and Stysz 2008 ), confirmed that mine dump material and soils there contain up to 427 mg kg −1 Sb. Elevated concentrations of Sb in soils should also be expected in the sites of former arsenic and polymetallic ore mining and processing, such as Złoty Stok, Czarnów, and Radzimowice (Karczewska et al 2007 , 2013 ; Krysiak and Karczewska 2007 ; Kabała 2015 ), as Sb occurs in those ores as an accompanying element (Mikulski 2010 ; Wilson et al 2013 ; Macgregor et al 2015 ). The soils of two Lower Silesian shooting ranges, in Wrocław and Oleśnica, turned out to contain enhanced concentrations of Sb, as it was revealed in our introductory study (Lewińska et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, compared to other pollutants, such as arsenic (As) and mercury (Hg), Sb is much less studied. Nonetheless, it can be more mobile than other pollutants such as As and Pb [6,7]. Recent studies even show that Sb mobility in soils was underestimated in early studies, especially in contaminated areas [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all elements present in sediment are equally susceptible to leaching upon interacting with water. Readily leachable or recalcitrant forms of elements vary largely and depend on the chemical forms of the elements in the sediment (Kwon and Lee 2001;Macgregor et al 2015;Pandey et al 2015). In addition, release of elements from contaminated sediment is effected by environmental conditions such as pH, phosphate, redox conditions, and time (Rubinos et al 2011;Molinari et al 2014;Dang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, release of elements from contaminated sediment is effected by environmental conditions such as pH, phosphate, redox conditions, and time (Rubinos et al 2011;Molinari et al 2014;Dang et al 2014). Although there are many studies about As mobilization and release from soils or sediments in mining areas (Paikaray 2015;Macgregor et al 2015;Desbarats et al 2015), quantitative information regarding the leaching of As in stream sediment in mining areas, particularly under hydrodynamic conditions, is rare.…”
Section: Introductionmentioning
confidence: 99%